The use of biocompatible composite scaffolds in oncology - O. I. Kit; A. Yu. Maksimov; I. A. Novikova; A. S. Goncharova; E. A. Lukbanova; A. O. Sitkovskaya; V. G. Volovik; S. V. Chapek (Сибирский онкологический журнал)
Modern tissue engineering approaches are aimed at developing scaffolds that contribute to the development of the whole variety of intercellular interactions that imitate those in a real object.The purpose of the study was to collect and summarize the data on the creation and use of three-dimensional cellular matrices.Material and Methods. A systematic literature search was conducted in the PubMed, Medline, Cyber Leninka and Elibrary databases. Out of the 315 articles searched, 38 were selected for this review.Results. A review of studies devoted to the development of three-dimensional composite structures (scaffolds) and their application in the field of cellular technologies was carried out. Methods for the manufacture of biocompatible structures using both natural biomaterials and synthetic ones, including various hydrogels and titanium alloys, were considered, and some physical and chemical characteristics were also discussed. The review discussed possible applications of 3D composite structures in oncology as one of the possible tools for expanding the fundamental understanding of the patterns of development of the malignant process, but also for use in the development of effective methods of treatment and the search for new drugs. The prospects for the use of scaffolds in the field of experimental oncology, namely in the creation of various types of tumor models, were outlined.Conclusion. Currently, three-dimensional culture systems are replacing two-dimensional models. Advances in this direction are associated with the creation and development of various variants of cell matrices that contribute to the solution of a number of applied problems in the field of creating three-dimensional tumor models in vitro and in vivo, therapy of malignant tumors and restorative medicine.